A Baseline Model For Estimating the Risk of Gas Embolism in Sea Turtles During Routine Dives - Robinson, Nathan J.; García-Párraga, Daniel; Stacy, Brian A.; Costidis, Alexander M.; Blanco, Gabriela S.; Clyde-Brockway, Chelsea E.; Haas, Heather L.; Harms, Craig A.; Patel, Samir H.; Stacy, Nicole I.; Fahlman, Andreas (Frontiers in Physiology, 2021)
Sea turtles, like other air-breathing diving vertebrates, commonly experience significant gas embolism (GE) when incidentally caught at depth in fishing gear and brought to the surface. To better understand why sea turtles develop GE, we built a mathematical model to estimate partial pressures of N2 (PN2), O2 (PO2), and CO2 (PCO2) in the major body-compartments of diving loggerheads (Caretta caretta), leatherbacks (Dermochelys coriacea), and green turtles (Chelonia mydas). This model was adapted from a published model for estimating gas dynamics in marine mammals and penguins. To parameterize the sea turtle model, we used values gleaned from previously published literature and 22 necropsies. Next, we applied this model to data collected from free-roaming individuals of the three study species. Finally, we varied body-condition and cardiac output within the model to see how these factors affected the risk of GE. Our model suggests that cardiac output likely plays a significant role in the modulation of GE, especially in the deeper diving leatherback turtles. This baseline model also indicates that even during routine diving behavior, sea turtles are at high risk of GE. This likely means that turtles have additional behavioral, anatomical, and/or physiologic adaptions that serve to reduce the probability of GE but were not incorporated in this model. Identifying these adaptations and incorporating them into future iterations of this model will further reveal the factors driving GE in sea turtles.